The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.34172/jlms.2021.02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Laser Treatments on Some Properties of the Zirconia-Porcelain Interface

Abstract: Introduction: This study was performed to compare the effect of Fractional CO2 laser or Q switched Nd:YAG laser of surface treatment on the shear bond strength of zirconia-porcelain interface. Methods: Fractional CO2 laser at 30 W, 2 ms, time interval 1 ms, distance between spots 0.3 mm, and number of scans is (4) or Q switched Nd:YAG laser at 30 J/mm2 and 10 Hz were used to assess the shear bond strength of zirconia to porcelain. Pre-sintered zirconia specimens were divided into three groups (n = 10) accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In this study, the tested zirconia substrates airabraded with 50 µm alumina oxide showed appropriate roughness to advance the bond of the repair material to the veneer ceramic and core zirconia. Surface modification by laser application has been recommended by many authors as an alternative method to change the surface texture of zirconia, enhance surface topography, 33 and surface roughness, 34,35 and activate micromechanical bonding to the resin repair material. 36 Laser effects on zirconia could be inherent in ablation or vaporization, which is reasoned as a microexplosion of portions of material heated higher than the melting point.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the tested zirconia substrates airabraded with 50 µm alumina oxide showed appropriate roughness to advance the bond of the repair material to the veneer ceramic and core zirconia. Surface modification by laser application has been recommended by many authors as an alternative method to change the surface texture of zirconia, enhance surface topography, 33 and surface roughness, 34,35 and activate micromechanical bonding to the resin repair material. 36 Laser effects on zirconia could be inherent in ablation or vaporization, which is reasoned as a microexplosion of portions of material heated higher than the melting point.…”
Section: Discussionmentioning
confidence: 99%
“…The surface conditioning of tooth structures and dental materials are some of the most prevalent laser applications in dentistry. Ceramic substrates can be conditioned using several technologies, including Er:YAG, Nd:YAG, Er, Cr, YSGG, and CO 2 lasers [11]. The preference for this recently created approach is increasing owing to its safety and efficacy [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The veneering materials do not have the sufficient mechanical properties compared to the zirconium suprastructure. Thus, a strong connection of both materials is the deciding factor [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The zirconium-based restorations in dental prosthetics transfer load up to 750 N [ 6 , 10 ]. The prosthetic zirconium dioxide ZrO 2 is made of grains of the order of (0.2–0.3) µm and does not contain the glass phase.…”
Section: Introductionmentioning
confidence: 99%